(3cTa GdQehRs - (3GdMSf Hf Ydj Hf CHj WGdH GdgGTej GdbQTj, CHh eMeO,J (B50 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3Ge HYO adeG habfi QiYXeJ fYeJg GQTGO GdeUGdM s
(3BNQgG (B:s
(3jJVef TQM GdcJGH Hjf hjLhR SHb ai GdejOGfjf s
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B199s
Keywords: (3abg GdePGgH GdCNQis